A dynamic simulation model for economic feasibility of apartment development projects - Lee, Kwangchae; Son, Seunghyun; Kim, Doyeong; Kim, Sunkuk (International Journal of Strategic Property Management, 2019)
Many factors influence the success of apartment development projects, but it is difficult to quantitatively measure them. In terms of risk control, the five most direct influence factors are sales ratio, unit sale price, financial cost, land cost, and construction cost. These factors will vary during the project, from planning to land purchase to design to sale to construction, and the levels of these factors will also affect project performance. Therefore, it is necessary to dynamically forecast, control and monitor, and manage these factors in order to successfully implement apartment development projects. This study develops a dynamic simulation model to analyze the economic feasibility of apartment development projects. It draws a causal loop diagram of the aforementioned influence factors, develops a simulation model using system dynamics, and verifies the model with a case study of a 1,794-unit apartment development project. Using this simulation model, it is possible to quickly and easily simulate the economic effects of the risk factors that change throughout the project, analyze its economic feasibility, and develop a plan to reduce economic losses, if necessary. The simulation model can also identify the optimal conditions for project feasibility and develop a risk-control model for apartment development projects.